Pengaruh persepsi online store dan offline store pada persepsi nilai dan dampaknya terhadap minat beli pada produk fashion - Mariah Mariah; Dewi Nurbaiti (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2019)
This study aimed to analyze the effect of the perception of online stores and offline stores to perceived value and its impact on buying interest fashion products in Jakarta. This study has a quantitative type of research with respondents of 100 consumers in Jakarta. The sampling method is purposive sampling. This study uses a quantitative research method by conducting a survey and the hypothesis test is done by path analysis method. The results of this study indicate that online perception is not a determinant of perceived value, while offline perception is proven to significantly affect perceived value of fashion products. In buying interest, perceived value is the only factor that can be considered as a determinant of buying interest in fashion products.